2019
DOI: 10.3389/fphys.2019.00197
|View full text |Cite
|
Sign up to set email alerts
|

Starvation Stress Causes Body Color Change and Pigment Degradation in Acyrthosiphon pisum

Abstract: The pea aphid, Acyrthosiphon pisum (Harris), shows body color shifting from red to pale under starvation in laboratory conditions. These body color changes reflect aphid’s adaptation to environmental stress. To understand the color-shifting patterns, the underlying mechanism and its biological or ecological functions, we measured the process of A. pisum’s body color shifting patterns using a digital imagery and analysis system; we conducted a series of biochemical experiments to determine the mechanism that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Silencing of CdeB prolonged nymph development duration in the present generation, altered the body weight and age structure, and significantly decreased the total aphid population number. Several studies have suggested that the red pigment could be used as a backup energy source that influences body length, body weight, finding of new hosts, and starvation resistance …”
Section: Discussionmentioning
confidence: 99%
“…Silencing of CdeB prolonged nymph development duration in the present generation, altered the body weight and age structure, and significantly decreased the total aphid population number. Several studies have suggested that the red pigment could be used as a backup energy source that influences body length, body weight, finding of new hosts, and starvation resistance …”
Section: Discussionmentioning
confidence: 99%
“…This might include stress conditions that affect resource vulnerability to attack by the consumer, for example through a change in morphology (e.g. stress‐induced changes in aphid body colour that alter their location by predators: Losey, Harmon, Ballantyne, & Brown, 1997; Wang et al, 2019) or effects on emission of volatile signals such as herbivore‐induced plant volatiles used for host location (see Stenberg, Heil, Åhman, & Björkman, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Acyrthosiphon pisum, an important crop pest [16] and eco-evo model organism [17], shows impressive phenotypic plasticity, a phenomenon of producing variable phenotypes in response to environmental stress [18,19]. Reproductive, ontogenetic, and phenotypic plasticities are contextual and may differ across polymorphic lineages, including green and pink morphs, underlined by metabolic differences [21][22][23][24][25]. The optimal temperatures for A. pisum range from 20°C to 25°C, with upper limits up to 30°C, depending on the geographic location and adaptability of aphid lineages [13].…”
Section: Introductionmentioning
confidence: 99%